2015
DOI: 10.5489/cuaj.2745
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopy in proximal ureteral stones after shock wave lithotripsy failure: Is it safe and efficient or dangerous?

Abstract: Complementary URS may be used safely after SWL failure in proximal ureteral stones. Its success rate and morbidities are similar to primary URS, except for longer operation time and an increased need for balloon dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 19 publications
(25 reference statements)
3
24
0
Order By: Relevance
“…In a study by Kilinc et al , URS was performed safely and successfully after SWL [ 14 ]. Patients whose stones are broken with SWL but do not achieve spontaneous passage or develop steinstrasse may have difficulty with endoscopic procedures due to ureteral stricture or stone-related mucosal injury and oedema.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Kilinc et al , URS was performed safely and successfully after SWL [ 14 ]. Patients whose stones are broken with SWL but do not achieve spontaneous passage or develop steinstrasse may have difficulty with endoscopic procedures due to ureteral stricture or stone-related mucosal injury and oedema.…”
Section: Discussionmentioning
confidence: 99%
“…Kilinc et al [15] compared the success and complication rates in patients with "complementary URS after previous unsuccessful ESWL" with "URS as first-line modality." They found that success rates of complementary and primary URS were 78.9 and 80.9%, respectively ( p = 0.57).…”
Section: Discussionmentioning
confidence: 99%
“…Although SWL is the recommended first-line treatment and can be performed as a non-invasive outpatient procedure, its disadvantages include need for auxiliary procedures, long duration of treatment, inability to dissect a large or impacted stone, anatomical and physical abnormalities of patients, and technical difficulties [15] . In recent years, with the improvement in the designs of ureterorenoscopes, stone disintegration systems, and endourologic techniques, most ureteral stones can be managed by URS [9] .…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, URS is often employed as salvage therapy in SWL-resistant stones. However, only a few studies (7)(8)(9)(10)(11)(12)(13) have determined the impact of previous unsuccessful SWL on the outcomes of URS with conflicting results. Holland et al reported that URS was associated with a lower SFR and higher complication rate when performed after unsuccessful SWL (7).…”
Section: Introductionmentioning
confidence: 99%
“…Irer et al also demonstrated that complications were significantly higher in patients with a previous SWL (8). In contrast, several studies showed that previous failed SWL had no impact on the SFR and complications of URS (9)(10)(11)(12)(13). Therefore, we conducted a meta-analysis, for the first time, to compare the outcomes of URS performed as a primary procedure (SWL−) and salvage URS (SWL+) after failed SWL.…”
Section: Introductionmentioning
confidence: 99%